2021
DOI: 10.3390/ph14030210
|View full text |Cite
|
Sign up to set email alerts
|

Design of Topical Ocular Ciprofloxacin Nanoemulsion for the Management of Bacterial Keratitis

Abstract: Bacterial keratitis (BK) is a critical ocular infection that can lead to serious visual disability. Ciprofloxacin (CIP), moxifloxacin (MOX), and levofloxacin (LFX) have been accepted as monotherapies by the US Food and Drug Administration for BK treatment. CIP is available commercially at 0.3% w/v concentration as an ophthalmic solution and as an ointment for ocular delivery. Because of solubility issues at physiological pH, CIP precipitation can occur at the corneal surface post instillation of the solution d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 67 publications
0
47
0
Order By: Relevance
“…Surfactants (Poloxamer 188 and Soyalecithin) were used to prepare the aqueous phase. Poloxamer 188 is a non-ionic surfactant, added to the lipid nanoformulations as a steric stabilizer, to promotes electrostatic stabilization because it decreases the electrostatic repulsion between the nanoparticles by creating a coat around the surface for keeping the stability of lipid nanoparticles [29,41].…”
Section: Ir-slns and Ir-cd-slnsmentioning
confidence: 99%
“…Surfactants (Poloxamer 188 and Soyalecithin) were used to prepare the aqueous phase. Poloxamer 188 is a non-ionic surfactant, added to the lipid nanoformulations as a steric stabilizer, to promotes electrostatic stabilization because it decreases the electrostatic repulsion between the nanoparticles by creating a coat around the surface for keeping the stability of lipid nanoparticles [29,41].…”
Section: Ir-slns and Ir-cd-slnsmentioning
confidence: 99%
“…Patel et al in their study showed that emulsions can increase the solubility and bioavailability of ocular drugs [35]. The oil in water (o/w) type of emulsion is generally preferred because of its better tolerance and low ocular irritation [40]. Liang et al proved that an emulsion enhanced the corneal permeation, precorneal residence time, sustained drug release, and bioavailability of the drug in male albino rabbits [41].…”
Section: Conventional Ocular Drug Delivery Systemmentioning
confidence: 99%
“…The nano-scale droplet size, thermodynamic activity, and low surface tension of NEs can disrupt skin barrier layers to facilitate drug delivery [ 149 ]. Tuning NEs droplet size, surface, viscosity facilitated successful topical ocular drug delivery by enhancing corneal permeation and drug absorption [ 145 , 150 ]. Ingestible NEs have been used to protect orally administered drugs from pH changes, enzymatic degradation, and the interaction with food byproducts.…”
Section: Insights Into Nanoemulsion Drug Delivery Mechanismsmentioning
confidence: 99%